Rancang Bangun Sistem Informasi Wedding Archive Management pada KUA Sukadiri Tangerang - Maulani, Giandari; Hia, Era Era; Annisa, Ufairotul (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
The Wedding Archive Management Information System at the KUA Sukadiri Tangerang is currently very much needed so that in managing the archiving of wedding document data for Sukadiri residents it can be more organized and easy to find. Previous problems occurred when filing arrangements related to Wedding Archive Management were not properly regulated, causing problems in the form of slow search of the required wedding document data until the data was scattered. The purpose of this study is to design and build a Wedding Archive Management information system for KUA Sukadiri Tangerang so that the arrangements for archiving marriage document data are well organized. This study applies data collection methods, PIECES system analysis methods, system design methods with UML diagrams, Visual paradigm, Black Box Testing, Laravel Framework and PHP programming language. The results of the research are in the form of a Web-based Wedding Archive Management Information System that can search wedding document data in a short time and has been implemented at KUA Sukadiri Tangerang.